Application of Calcium Phosphate Materials in Dentistry: A Review (Thamar University Journal of Natural & Applied Sciences, 2023)
Calcium phosphate materials are similar to bone in composition and having bioactive and osteoconductive properties. They have different forms, as cements, composites and coatings, which are used in many dental applications. This article reviews the latest update of their applications in dentistry the studies of improving the mechanical properties of these materials. Notable research is highlighted, regarding application of calcium phosphate into various fields in dentistry and improvement of their mechanical properties. This article deals with most common types of these materials including, calcium phosphate, hydroxyapatite and tricalcium phosphate. Keywords: Calcium phosphate materials, Dentistry, Hydroxyapatite, Tricalcium phosphate